2004
DOI: 10.1249/01.mss.0000117115.94062.e4
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward Obese Individuals among Exercise Science Students

Abstract: These results suggest that students in the field of exercise science possess negative associations and bias toward obese individuals. These findings have important implications for health promotion, as antifat bias and weight discrimination among exercise professionals may further contribute to unhealthy lifestyle behaviors and reduced quality of life for many obese individuals who are at high risk for chronic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
165
2
11

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(196 citation statements)
references
References 18 publications
18
165
2
11
Order By: Relevance
“…The purposes of this study were to examine antifat attitudes among physical educators, performance and ability expectations for normal and overweight youth, and perceptions of the problem of youth obesity and the role of schools and physical education. Consistent with previous research (Chambliss et al, 2004;Lewis et al, 1997), participants in this study endorsed moderate antifat attitudes and strong personal weight control beliefs. Crandall (1994) coined the phrase Note.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The purposes of this study were to examine antifat attitudes among physical educators, performance and ability expectations for normal and overweight youth, and perceptions of the problem of youth obesity and the role of schools and physical education. Consistent with previous research (Chambliss et al, 2004;Lewis et al, 1997), participants in this study endorsed moderate antifat attitudes and strong personal weight control beliefs. Crandall (1994) coined the phrase Note.…”
Section: Discussionsupporting
confidence: 89%
“…Further, antifat attitudes are problematic in that they might reduce or cancel out the effectiveness of programs designed to reduce rates of overweight and obesity among youth. 1 While obesity bias among physical education teachers has yet to be specifically examined, there is evidence that exercise and sport science students, a traditional major for future physical education teachers, do report antifat attitudes and obesity bias (Chambliss, Finley, & Blair, 2004). Thus, one purpose of this study was to examine the degree of antifat attitudes reported by members of the National Association for Sport and Physical Education (NASPE) within the American Alliance of Health, Physical Education, Recreation and Dance (AAHPERD).…”
Section: Introductionmentioning
confidence: 99%
“…A partir da análise dos dados verificou-se, como se havia hipotetizado, que em ambos os grupos de participantes houve uma atitude negativa no que se refere às pessoas obesas. Estes dados são comparáveis em amplitude àqueles de estudantes de Educação Física e de profissionais de saúde pesquisados nos Estados Unidos (CHAMBLISS;FINLEY;BLAIR, 2004;BROWNELL, 2001). A partir da análise, emerge ainda que a associação implícita entre "pessoas obesas" e "preguiça" é mais forte do que aquela entre "pessoas obesas" e "burrice": para a categoria entrevistada as limitações de movimento que as pessoas em estado de sobrepeso ou obesidade encontram são provavelmente fundamentais para sua condição.…”
Section: Discussionunclassified
“…A versatilidade do IAT foi demonstrada também por meio do desenvolvimento de uma forma impressa do instrumento (LOWERY; HARDIN; SINCLAIR, 2001;TEACHMAN et al, 2003), a qual mostrou-se de mais fácil aplicação na pesquisa desenvolvida e que já foi utilizada em estudos precedentes para avaliar o preconceito implícito no que diz respeito à obesidade em populações de profissionais que atuam em serviços de saúde (CHAMBLISS; FINLEY; BLAIR, 2004;BROWNELL, 2001). …”
Section: Teste De Associação Implícitaunclassified
“…The health implications of obesity are well documented, with increasing evidence that obese people are stigmatised and discriminated in various spheres of life such as healthcare [3][4], exercise settings [5][6] and more recently in the workplace [7][8]. It has been suggested that obesity represents one of the last acceptable forms of discrimination [9] based on the openness in which obese people are stigmatised in today's society.…”
Section: Introductionmentioning
confidence: 99%